Package Bids in Combinatorial Electricity Auctions: Selection, Welfare Losses, and Alternatives - Hübner, Thomas; Hug, Gabriela (Operations Research, 2026)
Day-ahead electricity auctions allow market participants to trade power for delivery the following day. In Europe, these auctions are designed as combinatorial auctions, enabling agents to submit package bids (“block bids”) that span multiple time periods rather than bidding separately for each hour. However, power exchanges impose limits on the number of package bids an agent can submit, creating a complex decision problem: Which packages should an agent bid on to best represent their preferences? In “Package Bids in Combinatorial Electricity Auctions: Selection, Welfare Losses, and Alternatives,” Hübner and Hug study this selection problem and propose decision-support algorithms that optimize bid choice under uncertainty. They provide theoretical bounds on welfare loss due to bid limits and validate their methods with simulations involving generators, storage systems, and flexible demand. Their findings offer actionable insights for both auctioneers and bidders.